The fall of the Ottomans : the Great war in the Middle East, 1914-1920 - Rogan, Eugene L. (London : Penguin, 2016)
Evaluates the impact of World War I on the Ottoman Empire and the Middle East as a whole, explaining the region's less-understood but essential contributions to the war and the establishment of present-day conflicts.
In 1914 the Ottoman Empire was depleted of men and resources after years of war against Balkan nationalist and Italian forces. But as the powers of Europe slid inexorably toward war, the Middle East could not escape the vast and enduring consequences of one of the most destructive conflicts in human history. The Great War spelled the end of the Ottomans, unleashing powerful forces that would forever change the face of the Middle East. Here, award-winning historian Eugene Rogan brings the First World War and its immediate aftermath in the Middle East to vivid life, uncovering the often ignored story of the region's crucial role in the conflict. Bolstered by German money, arms, and military advisors, the Ottomans took on the Russian, British, and French forces, and tried to provoke Jihad against the Allies in their Muslim colonies. Unlike the static killing fields of the Western Front, the war in the Middle East was fast-moving and unpredictable, with the Turks inflicting decisive defeats on the Entente in Gallipoli, Mesopotamia, and Gaza before the tide of battle turned in the Allies' favor. The postwar settlement led to the partition of Ottoman lands between the victorious powers, and laid the groundwork for the ongoing conflicts that continue to plague the modern Arab world. This book is essential reading for anyone seeking to understand the making of the modern Middle East.--From publisher description.
A revolution and three wars, 1908-1913 -- The peace before the Great War -- A global call to arms -- Opening salvos : Basra, Aden, Egypt, and the Eastern Mediterranean -- Launching jihad : Ottoman campaigns in the Caucasus and the Sinai -- The assault on the Dardanelles -- The annihilation of the Armenians -- The Ottoman triumph at Gallipoli -- The invasion of Mesopotamia -- The siege of Kut -- The Arab revolt -- Losing ground : the fall of Baghdad, the Sinai, and Jerusalem -- From armistice to armistice -- The fall of the Ottomans.
Includes bibliographical references (pages 409-458) and index.
English.
Keywords: 1288 - 1918; World War, 1914-1918 -- Campaigns -- Middle East; World War, 1914-1918 -- Turkey; World War, 1914-1918 -- Campaigns -- Turkey -- Gallipoli Peninsula; Military campaigns; Turkey -- History -- Ottoman Empire, 1288-1918.; Middle East; Turkey; Turkey -- Gallipoli Peninsula; History